METODE PENULISAN FIQH OLEH NUR AL-DIN AL-RANIRI DALAM KITAB AL-SIRAT AL-MUSTAQIM - Hashim, Jamalluddin; Ali, Abdul Karim (Jurnal Syariah, 2019)
Al-Sirat al-Mustaqim by Shaykh Nur al-Din al-Raniri (1600-1658M) is the oldest work on fiqh in Malay language ever known in South East Asia. It is not a comprehensive work on fiqh, but it deals only matters pertaining to‘ibadat. It was once regarded as an authoritative work in fiqh in Malay Archipelagoes particularly in Acheh. This article attempts to identify al-Raniri’s methods that was used in his al-Sirat al-Mustaqim regarding the content of the book, sources of his writing and his approach to discussing related issues. This article mainly relies on library research and it is a content analysis. Most of the data are collected or referred to the al-Sirat al-Mustaqim. This research discovered that the write up of the al-Sirat al-Mustaqim has been influenced by the writing of taqlid era, i.e. mazhab’s fanatism, lack of evidence and loaded with juristic views. Secondly, Shaykh Nur al-Din al-Raniri was a jurist who was able to exercise his ijtihad in several juristic issues. In other words, he has only rendered works of great Shafi’ie jurists to Malay language, and exercised his ijtihad.